PENGARUH KUALITAS MAKANAN TERHADAP LOYALITAS TAMU DI KALUAK PAKU RESTORAN HOTEL PANGERAN CITY PADANG - Fitrah Hayati; Lise Asnur (Ensiklopedia of Journal, 2023)
Such studies are quantitative studies using a casual association approach. The purpose of this study was to analyze the effect of food quality on guest loyalty in Kaluak Paku restaurant. The subjects of this study were 2050 guests who visited Kaluak Paku Hotel Pangeran City Padang Restaurant with a sample of 130 people. The sampling technique uses non-probability sampling. Data collection techniques are carried out by distributing Google Forms to guests visiting Kaluak Paku restaurant. Instrument tests are carried out by means of validity tests and reliability tests. Test Analysis is carried out by means of normality, homogeneity, and linearity tests. Hypothesis testing is performed by simple linear regression testing and coefficient of determination. The results of this study show that the quality of food at Kaluak Paku Restaurant Hotel Pangeran City has a positive effect on guest loyalty.